Cofactors in allergic reactions to food: physical exercise and alcohol are the most important. Issue 4 (15th September 2016) - Versluis, Astrid; van Os‐Medendorp, Harmieke; Kruizinga, Astrid G.; Blom, W. Marty; Houben, Geert F.; Knulst, André C.
Abstract: Introduction: Involvement of cofactors, like physical exercise, alcohol consumption and use of several types of medication, are associated with more severe food allergic symptoms. However, there is limited evidence on how often cofactors play a role in food allergic reactions. The study aimed to get more insight into the frequency of exposure to cofactors and how often cofactors are associated with more severe symptoms in food allergic patients. Methods: A questionnaire was completed by patients visiting the Allergology outpatient clinic. Patients with food allergy were included. Outcome measures were the frequency of medication use of medication groups that might act as cofactor and the frequency that physical exercise, alcohol consumption and use of analgesics are associated with more severe food allergic symptoms. Results: Four hundred ninety‐six patients were included in the study. The frequency with which patients used one or more types of medication that might act as cofactors was 7.7%: antacids/acid neutralizing medication (5%), NSAIDs (2%), beta blockers (0.6%), angiotensin‐converting enzyme inhibitors (0.6%), and angiotensin receptor blockers (0.2%). Of all patients, 13% reported more severe symptoms to food after involvement of one or more of the cofactors: physical exercise (10%), alcohol consumption (5%), and use of analgesics (0.6%). Sixty‐five percent did not know if these cofactors caused more severe symptoms; 22% reported that these cofactors had no effect. Conclusions: Only a small percentage of patients (7.7%) used medication that might aggravate food allergic reactions. Physical exercise and alcohol consumption were the most frequently reported cofactors, but occurring still in only 10% or less. Abstract : Involvement of cofactors, like physical exercise, alcohol consumption and use of several types of medication, are associated with more severe food allergic symptoms. This database study ( n  = 496) shows that only a small percentage of the food allergic patients (7.7%) used medication that might aggravate food allergic reactions and that physical exercise and alcohol consumption were the most frequently reported cofactors, but occurring still in only 10% or less. Our results indicated that it is important to increase the awareness both among patients and healthcare givers.